The epidemiology of Budd–Chiari syndrome in France. Issue 9 (September 2018) - Ollivier-Hourmand, Isabelle; Allaire, Manon; Goutte, Nathalie; Morello, Rémy; Chagneau-Derrode, Carine; Goria, Odile; Dumortier, Jerôme; Cervoni, Jean Paul; Dharancy, Sébastien; Ganne-Carrié, Nathalie; Bureau, Christophe; Carbonell, Nicolas; et al.
Abstract: Introduction: Epidemiological data is lacking on primary Budd–Chiari syndrome (BCS) in France. Methods: Two approaches were used: (1) A nationwide survey in specialized liver units for French adults. (2) A query of the French database of discharge diagnoses screening to identify incident cases in adults. BCS associated with cancer, alcoholic/viral cirrhosis, or occurring after liver transplantation were classified as secondary. Results: Approach (1) 178 primary BCS were identified (prevalence 4.04 per million inhabitants (pmi)), of which 30 were incident (incidence 0.68 pmi). Mean age was 40 ± 14 yrs. Risk factors included myeloproliferative neoplasms (MPN) (48%), oral contraceptives (35%) and factor V Leiden (16%). None were identified in 21% of patients, ≥2 risk factors in 25%. BMI was higher in the group without any risk factor (25.7 kg/m 2 vs 23.7 kg/m 2, p < 0.001). Approach (2) 110 incident primary BCS were admitted to French hospitals (incidence 2.17 pmi). MPN was less common (30%) and inflammatory local factors predominated (39%). Conclusion: The entity of primary BCS as recorded in French liver units is 3 times less common than the entity recorded as nonmalignant hepatic vein obstruction in the hospital discharge database. The former entity is mostly related to MPN whereas the latter with abdominal inflammatory diseases.